Analysis of Tasks and Activities in ESL Pronunciation Books at an Elementary Level (A1, A2) - Andršová, Barbora (Univerzita Pardubice, 2016)
The thesis analyses the rubrics and tasks in pronunciation coursebooks. In the first part of the paper, a certain attention is paid to the pronunciation features, which are vital to understand. Furthermore, the essential features of coursebooks, tasks and rubrics are explained. The second part of the paper deals with the evaluation of the rubrics and tasks regarding perception and production. Last but not least, the classification of tasks is examined according to the revised Bloom's Taxonomy.
Analýza zadání úloh a úkolů v odborných publikacích zaměřených na výslovnost angličtiny na úrovních A1 a A2
Keywords: výslovnost; učebnice; zadání úloh; úkoly; percepce; produkce; pronunciation; coursebook; rubrics; tasks; perception; production